Comparative analysis of the effectiveness of different training programs for athletes of high qualification, specializing in rowing - Міфтахутдинова Діна Артурівна, (Dina Miftahutdinova) (Slobozhanskyi Herald of Science and Sport, 2015)
Purpose: to evaluate the efficiency of different programs of training sessions to improve operational preparedness qualified athletes who specialize in rowing. Materials and Methods: the study included 10 athletes craftsmanship that are part of the national team of Ukraine rowing. To assess the functional training using computer program "SHVSM" and submaximal test PWC170. Results are content authoring program training sessions to improve functional training highly skilled athletes who specialize in rowing and academic results its experimental verification. Conclusions: the experiment confirmed a higher efficiency of the program of training sessions for rowing-sportsmen team Ukraine compared with the program, which is traditionally used, as evidenced by the survey.